Association between angiotensin converting enzyme gene insertion/deletion polymorphism and ischemic stroke in north Indian population: a case–control study and meta-analysis. (September 2014) - Kumar, Amit; Vivekanandhan, S.; Srivastava, Arpna; Tripathi, Manjari; Padma Srivastava, M. V.; Saini, Neha; Kumar, Pradeep; Prasad, Kameshwar
<x content-type="archive" xml:space="preserve">Abstract</x> Objective: The purpose of this case–control study was to determine the relationship between angiotensin converting enzyme (ACE) insertion/deletion polymorphism and serum ACE level in north Indian patients with ischemic stroke. Methods: In the present study, 224 ischemic stroke patients and 224 age- and sex-matched control participants were recruited. Genotyping was performed using polymerase chain reaction (PCR) method. Serum ACE levels were measured by colorimetric method. Our results were integrated with other reported studies from India for a meta-analysis. Results: We observed that DD genotypes were more frequently distributed in cases (32·6%) compared with controls (26·8%). Borderline significance was observed between DD genotype and risk of small vessel disease (SVD) stroke as compared to controls (OR, 1·9; 95% CI, 0·88-4·4; P value 0·09) assuming dominant model of inheritance. The mean ACE serum level in IU/l for II, ID, and DD genotypes were 17·1 ± 7·7, 26 ± 12·4, and 51·3 ± 21 (P value < 0·001) in cases and 16·5 ± 9·4, 26·8 ± 13, and 45·19 ± 18·3 (P value < 0·001) in controls, respectively. Discussion: The results of the study show lack of significant association between ACE insertion/deletion polymorphism and ischemic stroke, however, higher risk was observed with DD genotype in small vessel disease stroke, but with borderline significance. Meta-analysis of studies from India showed that DD genotype is associated with risk of ischemic stroke.